Implementation of Raw Material Inventory Control System to Increase Sales of Hand Batik: Implementasi Sistem Pengendalian Persediaan Bahan Baku Untuk Meningkatkan Penjualan Batik Tulis - Fajri, Rihan; Nurasik, Nurasik (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to explain about how to control the supply of raw materials in the Batik Tulis Trading Business